ISOLASI DAN KARAKTERISASI MORFOLOGI DAN FISIOLOGI BAKTERI ENDOFIT DARI TANAMAN BUAH NAGA MERAH (Hylocereus polyrhizus) - Afriani, Imas; Puspita, Fifi; Ali, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Endophytic bacteria are bacteria that live in plant tissue, including in dragon fruit plant tissue. There are many species of endophytic bacteria living inside tissue dragon fruit plant wich play a beneficial role for plant. Endophytic bacteria can be used as a biological fungicide and biological fertilizer which are useful for plants. The purpose of the research is to observe the characteristics of the endophytic bacteria. Plants samples was taken by using purposive sampling method. The location is at Balai Pelatihan dan Pengembangan Masyarakat PT. Arara Abadi the district of Siak Riau. Plant tissues were taken from roots and shoots of the dragon fruit plants. The data were analyzed descriptively. Results showed that the morphological characterization of endophytic bacteria such as colonies color, colonies form and colonies elevation had some similarities each others, but there was a difference on the edges of colonymorphology. Two isolates had a flat edges and three isolates have wavy edges. Physiologycal assays such as catalase assay, oxidase assay and starch hydrolysis assay of the bacteria showed a positive on the each isolate, but there was a difference on the motility assay and indole assay. Two isolates showed that they were motile and positive indole assay,while the three other isolates showed that they were non-motile and indol negative assay.Based on the morphological and physiological similarities of the endophytic bacteria, it can be assumed the bacteria belong to Genera of Bacillus and Corynebacterium. Keyword : Isolation and characterization, endophytic bacteria, and dragon fruit plant